The occurrence of clubroot in cruciferous crops correlates with the chemical and microbial characteristics of soils - Kang, Huajun; Lin, Zihan; Yuan, Xiaowei; Shi, Yanxia; Xie, Xuewen; Li, Lei; Fan, Tengfei; Li, Baoju; Chai, Ali (Frontiers in Microbiology, 2024)
Clubroot disease, caused by Plasmodiophora brassicae, is a serious soil-borne disease in Brassica crops worldwide. It seriously occurs in conducive soils of southern China, while never happens in some areas of northern China with suppressive soils. To understanding the differences, we measured the soil suppressiveness, chemical properties and microbial communities in suppressive and conducive soils by bioassay and sequencing of 16S rRNA and 18S rRNA amplicons. The biological basis of clubroot suppressiveness was supported by the ability to remove it by pasteurization. The pH value and calcium content in the suppressive soils were higher than those in the conducive soils. Suppressive soils were associated with higher fungal diversity and bacterial abundance. The fungal phyla Chytridiomycota, Olpidiomycota, and Mucoromycota and the bacterial phyla Acidobacteriota and Gemmatimonadota were enriched in suppressive soils. More abundant beneficial microbes, including Chaetomium and Lysobacter, were found in the suppressive soils than in the conducive soils. Molecular ecological network analysis revealed that the fungal network of suppressive soils was more complex than that of conducive soils. Our results indicate that plant health is closely related to soil physicochemical and biological properties. This study is of great significance for developing strategies for clutroot disease prevention and control.